Evaluating the Energy Sustainability of Urban Agriculture Towards More Resilient Urban Systems - Ghisellini, Patrizia; Casazza, Marco (Journal of Environmental Accounting and Management, 2026)
Food is the primary energetic need for humankind. It provides energy and nutrients, but its acquisition requires energy expenditure. This fact is particularly important, when considering the urban environment, since human communities organized within cities almost exclusively rely on the import of resources to meet their daily basic needs. Field-to-fork chain and its energetic cost depends on the organization of the food production and transformation processes, which, in turn, can be influenced by the city-countryside relationship idea and the organization of both the urbanization process and the agricultural production. A solution might come from the urban agriculture development and management. A short review of the state-of-theart about urban agriculture, energy and urban resilience is given, together with an historical overview of the city-countryside relationship idea development, which still influences the evolution of urban agriculture. The results show that urban agriculture in the different forms partially contribute to address food security in urban centres both in developed and developing countries. It also provides many environmental, economic and social benefits. However, in particular the energetic and environmental impacts of the different forms should be widely investigated on-site to understand whether UA is a sustainable option.